Penggunaan E-Learning Sebagai Media Interaktif Dalam Pembelajaran Dalam Jaringan (Daring) - ., Faisal Al Fasih; ., Sulystiani; ., Putri Farhani; ., Ali Ikhwan (CV. ITTC INDONESIA, 2022)
Technology was an important role in the world of education, especially in the teaching and learning process where during the spread of the Covid-19 virus, all activities were transferred to remote or online (online) including learning carried out remotely through various technological media, one of the technologies used This is E-Learning, where e-learning is considered efficient in collecting assignments and providing learning materials, but even though online learning is considered to have advantages and looks fun because it can be done from home, it is not easy to do. This study aims to find out how important the use of E-learning is in the teaching-learning process during the Covid-19 period.